1970
DOI: 10.2355/isijinternational1966.10.163
|View full text |Cite
|
Sign up to set email alerts
|

On the Morphology of Strain-Induced Martensite and the Transformation-Induced Plasticity in Fe-Ni and Fe-Cr-Ni Alloys

Abstract: Synopsis [n order to study the morphology q[ strain-induced martensite and the plasticity induced by the martensitic transformation, tellsile tests at various temperatures were carried out using Fc-31% N i, Fe-29%N i-O.26% C and Fe-15% Cr-13%N i alloys whose Ms temperatures u:ere below room temjlerature and the microstructures were observed. The results obtained are summarized as fo llows. In Fe-Ni and Fe-Ni-C alloys, a characteristic martensite whose morphology is entirely different fiom that of thermalfv tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…In addition to the chemical composition of austenite, such as the amount of carbon in solid solution, the M S temperature, stacking fault energy [1][2][3][4][5][6][7] and microstructural factors such as grain size, [7][8][9][10][11] morphology [12][13][14] and crystal orientation 15,16) of austenite, the transformation behavior is also heavily dependent on the stress state 17) and deformation temperature. [18][19][20] The trans-formation mechanism varies but is mainly dependent on the deformation temperature. As the temperature exceeds M S , stress-induced martensitic transformation occurs during the elastic deformation of austenite in a similar manner as found in thermally induced regular martensite.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the chemical composition of austenite, such as the amount of carbon in solid solution, the M S temperature, stacking fault energy [1][2][3][4][5][6][7] and microstructural factors such as grain size, [7][8][9][10][11] morphology [12][13][14] and crystal orientation 15,16) of austenite, the transformation behavior is also heavily dependent on the stress state 17) and deformation temperature. [18][19][20] The trans-formation mechanism varies but is mainly dependent on the deformation temperature. As the temperature exceeds M S , stress-induced martensitic transformation occurs during the elastic deformation of austenite in a similar manner as found in thermally induced regular martensite.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies regarding the microstructural characteristics of deformation-induced martensite focus on single-phase austenitic high alloy TRIP steels. For instance, studies using Fe-Ni alloys 19,20) showed that deformation-induced martensite subjected to tensile deformation above the M S temperature is typical lenticular martensite with a midrib. However, in contrast to the deformation mechanism of athermal martensite, deformation-induced martensite subjected to tensile deformation at higher temperatures has no mid-rib or deformation twins but instead forms notably fine butterfly martensite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tamura et al . 56 interpreted that strain softening was caused by the normal slip deformation and the deformation due to ε-martensite formation. Bhadeshia et al .…”
Section: Discussionmentioning
confidence: 99%
“…The use of steel with a martensitic structure having the highest hardness has also been considered. [4][5][6][7][8] However, although it shows high strength, the steel made by these methods has poor ductility and processability. 9,10) Recently, carbon clusters have attracted attention in the steel industry as an effective material for overcoming this disadvantage.…”
Section: Introductionmentioning
confidence: 99%